Analysis of the Association of Foramen Cecum and Dens in Dente in Maxillary Lateral Incisor - Genaro, Luis Eduardo [UNESP]; Conte, Marcelo Brito [UNESP]; Anovazzi, Giovana [UNESP]; Gonçalves, Andréa [UNESP]; Gonçalves, Marcela De Almeida [UNESP]; Capote, Ticiana Sidorenko De Oliveira [UNESP] (Thieme, 2021)
Objectives The aim of this study was to evaluate the frequency of foramen cecum and dens in dente, and to verify the association of these structures in the maxillary lateral incisor (MLI). Materials and Methods The presence of foramen cecum in the lingual surface of 110 MLI was verified, and the teeth were radiographed to observe the presence of dens in dente, being classified according to the literature. An association study between the presence of foramen cecum and dens in dente was performed using the Cramer's V and chi-square statistical tests. Results The association was statistically significant between the foramen cecum and the dens in dente. Concomitant presence was observed in 17.27%, being a high rate when compared with the presence of foramen cecum alone (9.09%) or dens in dente alone (8.18%). In addition, type I (minimal invagination, confined to the crown of the tooth and not extending beyond the level of the cementum-enamel junction) was the most frequent (82.14%). Conclusions We emphasize the importance of alerting the dentist to the presence of a foramen cecum on the lingual surface of the MLI, as it is likely that dens in dente is usually of type I. Thus, the foramen cecum is a sign that can assist the dental surgeon in the discovery of dens in dente and clinical conduct to be taken.
Keywords: anatomy; dens in dente; incisor